2021
DOI: 10.12998/wjcc.v9.i8.1946
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia followed by epidural hydroxyethyl starch prevented post-dural puncture headache: Twenty case reports and a review of the literature

Abstract: BACKGROUND Accidental dural puncture (ADP) and subsequent post-dural puncture headache (PDPH) remain common complications of epidural procedures for obstetric anesthesia and analgesia. No clear consensus exists on the best way to prevent PDPH after ADP. CASE SUMMARY We report our findings in twenty parturients who underwent an incorporated strategy of epidural analgesia followed by epidural hydroxyethyl starch (HES) to prevent PDPH after ADP with a 16-gauge Tuohy needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[ 40 ] Two case series on the utility of epidural HES mostly for PDPH prophylaxis after obstetric ADP including 8 and 20 patients, respectively, reported that no serious adverse effects such as neurological deficits were detected. [ 22 , 41 ] Two recent rat studies indicated that single or repeated intrathecal injection of HES did not induce any clinical or histopathological evidence of long-term neuronal toxicity. [ 42 , 43 ] Although no adverse events potentially associated with epidural HES were reported, safety evidence should be sought further in this circumstance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 40 ] Two case series on the utility of epidural HES mostly for PDPH prophylaxis after obstetric ADP including 8 and 20 patients, respectively, reported that no serious adverse effects such as neurological deficits were detected. [ 22 , 41 ] Two recent rat studies indicated that single or repeated intrathecal injection of HES did not induce any clinical or histopathological evidence of long-term neuronal toxicity. [ 42 , 43 ] Although no adverse events potentially associated with epidural HES were reported, safety evidence should be sought further in this circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating epidural volume extension using colloids in combined spinal–epidural anesthesia for cesarean delivery, 33 pregnant patients received epidural 6% HES 200/0.5 and did not report any neurologic deficits postoperatively [40] . Two case series on the utility of epidural HES mostly for PDPH prophylaxis after obstetric ADP including 8 and 20 patients, respectively, reported that no serious adverse effects such as neurological deficits were detected [22,41] . Two recent rat studies indicated that single or repeated intrathecal injection of HES did not induce any clinical or histopathological evidence of long-term neuronal toxicity [42,43] .…”
Section: Discussionmentioning
confidence: 99%
“…178 In a retrospective case series, Song et al assessed the effectiveness of injecting HES 6% solution 15 mL into the epidural space to prevent PDPH after an inadvertent dural puncture. 179 The authors concluded that this was highly effective in preventing the occurrence of PDPH. However, a limitation was that the injection of HES was performed 24 hours after using an epidural catheter to provide analgesia; therefore, it is unclear which intervention was effective.…”
Section: Original Researchmentioning
confidence: 99%